Natural occurence of mycorrhiza Rhizobium phaseoli in areas under beans cultivation - Saito, S.M. Tsai; Martins, Eleonora C.S.; Freitas, J. R. de; Roston, A.J. (Pesquisa Agropecuaria Brasileira, 2014)
Standard experimental plots 5 m x 5 m (10 rows of 5 m each) were set with the bean cultivar Carioca in 16 sites in the south of São Paulo State, Brazil, to determine the presence of native vesicular-arbuscular mycorrhiza (VAM) and native Rhizobium phaseoli. It was observed that Rhizobium phaseoli and VAM are present in those areas. In respect to Rhizobium, the abundant nodulation in the glasshouse and high number of Rhizobium in the soil (around 4 x 106 bact/g of soil), compared to the poor nodulation at those sites, indicate that environmental factors (mainly drought) limited nodule development under field condition. VAM infection varied between 13,3 to 83,3% in the field, with an average of 53% and between 6,6 to 53,3% in the glasshouse, averaging 32%. The spore numbers varied from 4 to 65 per 50 g of soil, with an average of 21 spores/50 g of soil. The higher occurrence of Rhizobium in the glasshouse when compared with that under field conditions, and the inverse response observed with VAM fungi indicate that diverse factors have acted on the establishment and survival of both microorganisms.